EDUCATION TO IMPROVE QUALITY OF LIFE OF PATIETS WITH STOMA: A LITERATURE REVIEW - Arifin Triyanto (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2021)
Several conditions or disease may necessitate the formation of stoma as a treatment. However, stomas has a negatif effect on physical, psychological, social and spiritual aspects that can reduce the quality of life. Education is an effort to improve the quality of life of patients with stoma. The aim of this study was to describe the education of patients with stoma to improve quality of life. A review of the literature by searching in sciencedirect, EBSCO, and pubmed. Four relevant articles include in syntesis. Three studies conclude that education can improve quality of life and one study did not show significant results, but there were positive changes in the quality of life value. Education is provided through a variety of methods, the topic covers various aspects of life, delivered by a team of health care, given at least 2 sessions. Education in patients with stomas can improve quality of life. Although each article has a different method of education, it has a positive effect on improving the quality of life.